Uso desigual del espacio recreativo público en el contexto de la COVID-19 en Lima Metropolitana - Chambi Chamorro, Gloria Estefany (2020)
The compulsory isolation produced by the Covid-19 pandemic has evidenced the need to be able to recreate or generate a social link, not only to enjoy physical well-being, but also mental well-being is really such: a necessity. Faced with the «new normality», the Peruvian government implemented measures for the reincorporation of individual recreational activities, so the need arises to analyze the socio-spatial inequalities to access a quality public recreational space near the place of residence, the use and frequency depending on the before, during and after quarantine, and the public policies that are being implemented for the proper use of public recreational spaces in Metropolitan Lima, which were evaluated through a virtual survey. It is concluded that it is necessary to provide quality spaces that ensure safe and equitable use that meet social and individual needs and avoid displacement in search of suitable spaces in other places, thus avoiding the increase of contagions.